Construction of Religious Moderation at Nahdlatul Ulama Online Media in East Java - Trio Mashuri, Akbar; Lubis, Abdul Rojak; Moefad, Agoes Moh (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This research focuses on how journalists at Nahdlatul Ulama (NU) Online Media in East Java construct news presented to the public about religious moderation. It showcases news framing on religious moderation from the perspective of Nahdlatul Ulama through online media in East Java. This research aims to understand how NU's religious moderation is disseminated in society through media produced by journalists. The research method employed is qualitative, utilizing media text analysis with framing by Zhondang Pan and Gerald M. Kosicki, analyzing four syntactic structures: script, thematic, and rhetorical. The research also involves validation of the truth and news construction with the editorial board of NU Online East Java. The results of this research explain that journalists at NU Online East Java construct news on religious moderation by presenting the teachings of Ahlus Sunnah Wal Jamaah Nahdliyah through the practice of Hubbul Watan Minal Iman (Love of the Homeland is Part of Faith), with the vision of Islam as a mercy to all creations (rahmat lil 'alamin). Conflicts arise in online media concerning narratives of violence, liberalization, and radicalism. Consequently, journalists construct the values of religious moderation from the perspective of NU figures, namely Alisha Wahid and Gus Miftah, to create alternative narratives in online media that promote positive content rather than content that divides intergroup relationships.